2020
DOI: 10.1111/geb.13160
|View full text |Cite
|
Sign up to set email alerts
|

Drought shrinks terrestrial upland resilience to climate change

Abstract: Aim Drought has been shown to alter terrestrial ecosystem carbon (C) and nitrogen (N) dynamics, and thus feedback to future climate. However, drought‐induced changes in terrestrial upland C and N pools and the drought response of soil carbon dioxide (CO2) and nitrous oxide (N2O) fluxes are yet to be quantified. Location Global upland ecosystems. Time period 2000–2018. Major taxa studied Terrestrial C and N fluxes. Methods A meta‐analysis was conducted that compiled 1,344 measurements from 128 manipulative stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Precipitation reduction may reduce soil N 2 O emissions directly through suppressing the growth and activities of N‐cycling microbes (i.e., nitrifiers and denitrifiers) (Borken & Matzner, 2009; Li et al, 2020). A meta‐analysis of 128 field experiments has recently shown that precipitation reduction significantly decreased N 2 O emissions in cropping and forest soils (Zheng et al, 2020), primarily because enhanced soil aeration is unfavorable for denitrification (Homyak et al, 2017; Zheng et al, 2020). Precipitation reduction may also affect soil N 2 O emissions indirectly by altering soil available N and/or C for nitrifiers and denitrifiers via reducing plant N uptakes, and/or photosynthate allocation belowground (Homyak et al, 2017; Shi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Precipitation reduction may reduce soil N 2 O emissions directly through suppressing the growth and activities of N‐cycling microbes (i.e., nitrifiers and denitrifiers) (Borken & Matzner, 2009; Li et al, 2020). A meta‐analysis of 128 field experiments has recently shown that precipitation reduction significantly decreased N 2 O emissions in cropping and forest soils (Zheng et al, 2020), primarily because enhanced soil aeration is unfavorable for denitrification (Homyak et al, 2017; Zheng et al, 2020). Precipitation reduction may also affect soil N 2 O emissions indirectly by altering soil available N and/or C for nitrifiers and denitrifiers via reducing plant N uptakes, and/or photosynthate allocation belowground (Homyak et al, 2017; Shi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The impacts of drought on soil functioning may depend on the duration of drought. In general, drought can depress CO 2 emissions and decrease soil dissolved organic C [ 17 ]. Meanwhile, the microbial community under drought may destabilize soil C [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that drought can influence soil microorganisms and underground nutrient cycling. Water deficits can evidently decrease soil respiration [ 17 ]. It is well-known that the soil microbial community is related to soil carbon cycling [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations